2016
DOI: 10.1007/s00421-016-3444-5
|View full text |Cite
|
Sign up to set email alerts
|

Does knee joint cooling change in vivo patellar tendon mechanical properties?

Abstract: PurposeThis study aimed to assess the influence of knee joint cooling on the in vivo mechanical properties of the patellar tendon.MethodsTwenty young, healthy women volunteered for the study. B-mode ultrasonography was used to record patellar tendon elongation during isometric ramp contraction of the knee extensors (5–7 s, 90° knee angle) and calculate tendon stiffness. Skin temperature was measured by infrared thermometry. Data were acquired before and after 30 min of local icing of the knee joint and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The data show that after the 6 weeks without training, the EI increased 91.2 ± 71.4% in EG1 with respect to baseline, which seems to indicate that eccentric exercise causes different long-term adaptations in the stiffness of the PT to isometric exercise, since Kubo et al [ 39 ] found a reduction in the stiffness of the tendon two months after completing a training program using isometric contractions. A higher value in the EI of the PT, such as that found in our study after six weeks without training, indicates greater stiffness, which may benefit the rate of force development [ 40 ], and it has been associated with better performance in agility tests, pace changes, sports with continuous stretch–shortening cycles and speed/sprint tests [ 41 ]. However, at the same time, the risk of muscle injury in the tendons with these characteristics is higher because the high stiffness makes the tendon absorb less energy and increases the forces that are generated in muscle [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…The data show that after the 6 weeks without training, the EI increased 91.2 ± 71.4% in EG1 with respect to baseline, which seems to indicate that eccentric exercise causes different long-term adaptations in the stiffness of the PT to isometric exercise, since Kubo et al [ 39 ] found a reduction in the stiffness of the tendon two months after completing a training program using isometric contractions. A higher value in the EI of the PT, such as that found in our study after six weeks without training, indicates greater stiffness, which may benefit the rate of force development [ 40 ], and it has been associated with better performance in agility tests, pace changes, sports with continuous stretch–shortening cycles and speed/sprint tests [ 41 ]. However, at the same time, the risk of muscle injury in the tendons with these characteristics is higher because the high stiffness makes the tendon absorb less energy and increases the forces that are generated in muscle [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…In this study, BT significantly decreased only with an icing period of 180 min. Previous studies reported that ice application of 30 min over the Achilles (14) and patellar (15) tendons decreased the skin temperature to approximately 17-20˚C. Furthermore, Dewhurst et al (16) reported that ice pack application over the thigh decreases skin temperature by 6˚C and muscle temperature by 4˚C.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study was to determine static (isometric) and dynamic (isokinetic) quadriceps strength following FKJC. If we found the expected improvements during isometric contraction that were consistently documented in the literature [20][21][22], the improvement would translate to isokinetic (dynamic) strength because of ice-induced mechanical changes [26] and/or neuromuscular facilitations [25,28]. We hypothesized that FKJC would significantly improve both isometric and isokinetic quadriceps strength as measured by peak torque output.…”
Section: Introductionmentioning
confidence: 86%